A Preliminary Study on Accident Rate in the Workplace through Occupational Safety and Health Management in Electricity Service - Amirrudin Abdul Aziz; Mohd Esa Baruji; Siti Nazhatul Marina Mior Iskandar Shah; Norsyahidah Mohammad Yusof; Nik Fadhilah Nik Him; Mohammad Noorizzuddin Nooh (Quest Journals, 2024)
Volume 2 Issue 12